Belatacept for Simultaneous Calcineurin Inhibitor and Chronic Corticosteroid Immunosuppression Avoidance: Two-Year Results of a Prospective, Randomized Multicenter Trial. Issue 9 (September 2021) - Kaufman, Dixon B.; Woodle, E. Steve; Shields, Adele Rike; Leone, John; Matas, Arthur; Wiseman, Alexander; West-Thielke, Patricia; Sa, Ting; King, Eileen C.; Alloway, Rita R.; ,
Visual Abstract: Abstract : Background and objectives: Immunosuppressive therapy in kidney transplantation is associated with numerous toxicities. CD28-mediated T-cell costimulation blockade using belatacept may reduce long-term nephrotoxicity, compared with calcineurin inhibitor–based immunosuppression. The efficacy and safety of simultaneous calcineurin inhibitor avoidance and rapid steroid withdrawal were tested in a randomized, prospective, multicenter study. Design, setting, participants, & measurements: This study reports the 2-year results of a randomized clinical trial of 316 recipients of a new kidney transplant. All kidney transplants were performed using rapid steroid withdrawal immunosuppression. Recipients were randomized in a 1:1:1 ratio to receive belatacept with alemtuzumab induction, belatacept with rabbit anti-thymocyte globulin (rATG) induction, or tacrolimus with rATG induction. The composite end point consisted of death, kidney allograft loss, or an eGFR of <45 ml/min per 1.73 m 2 at 2 years. Results: The composite end point was observed for 11 of 107 (10%) participants assigned to belatacept/alemtuzumab, 13 of 104 (13%) participants assigned to belatacept/rATG, and 21 of 105 (21%) participants assigned to tacrolimus/rATG (for belatacept/alemtuzumab versus tacrolimus/rATG, P =0.99; for belatacept/rATG versus tacrolimus/rATG, P =0.66). Patient and graft survival rates were similar between all groups. An eGFR of <45 ml/min per 1.73 m 2 was observed for nine of 107 (8%) participants assigned to belatacept/alemtuzuab, eight of 104 (8%) participants assigned to belatacept/rATG, and 20 of 105 (19%) participants assigned to tacrolimus/rATG ( P <0.05 for each belatacept group versus tacrolimus/rATG). Biopsy sample–proven acute rejection was observed for 20 of 107 (19%) participants assigned to belatacept/alemtuzuab, 26 of 104 (25%) participants assigned to belatacept/rATG, and seven of 105 (7%) participants assigned to tacrolimus/rATG (for belatacept/alemtuzumab versus tacrolimus/rATG, P =0.006; for belatacept/rATG versus tacrolimus/rATG, P <0.001). Gastrointestinal and neurologic adverse events were less frequent with belatacept versus calcineurin-based immunosuppression. Conclusions: Overall 2-year outcomes were similar when comparing maintenance immunosuppression using belatacept versus tacrolimus, and each protocol involved rapid steroid withdrawal. The incidence of an eGFR of <45 ml/min per 1.73 m 2 was significantly lower with belatacept compared with tacrolimus, but the incidence of biopsy sample–proven acute rejection significantly higher. Clinical Trial registry name and registration number: Belatacept Early Steroid Withdrawal Trial, NCT01729494